Anthropometric study of facial index of medical students - Pandey, Niraj; Gogoi, Parmananda; Budathoki, Deepesh; KC, Gopal (Journal of Kathmandu Medical College, 2017)
Background: The human facial contour has always been an interesting subject for anatomists, anthropologists, plastic surgeons and artists. The purpose of study was to create and evaluate data on face anthropometry. Objectives: To determine total facial index in medical students and to compare these with the data from other population for use in forensic, archaeological studies, anatomy and plastic surgery. Methods: This is a descriptive study. A total of one hundred and forty medical students, presently studying at Kathmandu Medical College, aged between eighteen and twenty four years were selected as the subjects for the present study. Among the one hundred and forty students, forty four were female and ninety six were male. Two measurements: morphological facial length and bizygomatic breadth were taken by using spreading calibre. Results: The mean morphological facial length was 110.7mm with a standard deviation of 5.98mm in males and 102.1mm in females. Bizygomatic breadth was 130.8 mm in males & 123.5mm in females. The facial index (mean) was 86.09 in males and 84.84 in females. The dominant type of face shape in males was mesoproscopic (48.66%) followed by euriprosopic (23%), leptoprosopic (13.33%), hypereuriprosopic (13%) & hyperleptoprosopic (2%). In females the dominant type of face was also mesoprosopic (37%) followed by hypereuriprosopic (22%), euriprosopic (20.33%), leptoprosopic (19%) and hyperleptoprosopic (1.66%). Conclusion: The dominant phenotype in the studied population was mesoprosopic. The data obtained may be useful in anthropological research, forensic, genetic research, as well as in medical clinical practice.